2021
DOI: 10.3390/machines9030054
|View full text |Cite
|
Sign up to set email alerts
|

Development of Digital Models of Interconnected Electrical Profiles for Rolling–Drawing Wire Mills

Abstract: The latest development trend in rolling industry is the combination of various technological operations in continuous production lines. In the production of long products, the combination of rolling and drawing processes looks promising. A wire drawing mill developed by the team of authors of this work belongs to the conceptually new, integrated lines. The creation of new integrated rolling mills requires a research phase, where relevant concepts are scrutinized using the methods of mathematical modeling. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For example, a 2021 study reported the available opportunities for reducing electric power consumption through the application of developed numerical models describing technological processes of wire drawing. The method is based on the use of the reserves of friction forces that are present during idling [129].…”
Section: Improved Operational Maintenancementioning
confidence: 99%
“…For example, a 2021 study reported the available opportunities for reducing electric power consumption through the application of developed numerical models describing technological processes of wire drawing. The method is based on the use of the reserves of friction forces that are present during idling [129].…”
Section: Improved Operational Maintenancementioning
confidence: 99%
“…Mathematical models of the UMD and LMD mechatronic systems, developed considering their linkage through metal, have been described in [53][54][55]. Dynamic drive modes at the roll slippage have been studied in [56][57][58].…”
Section: Simulation and Experimental Studiesmentioning
confidence: 99%
“…They also need to be adjusted for how the strip connects different components. The authors' papers [38][39][40] detail parts of the model.…”
Section: Simulation Model Structurementioning
confidence: 99%